Primary Herpes Simplex Virus Infection Mimicking a Cervical Malignancy in an Immunocompetent Individual - Clure, Cara (Cureus, 2018)
Herpes simplex virus (HSV) is a common sexually transmitted infection. Although primary HSV typically presents with ulcerations, atypical presentations are possible. Only one other case report of HSV manifesting as a cervical mass exists. A 35-year-old immunocompetent female with dysuria was found to have a cervical mass concerning for cancer. She had a history of abnormal pap smears and a loop electrosurgical excision procedure (LEEP) with poor follow-up. The patient was taken to the operating room for biopsies and staging and was found to have new vulvar ulcers. The biopsies confirmed an HSV infection with cervical, bladder, and vulvar involvement and were negative for cervical neoplasia. This report examines an atypical presentation of a primary HSV infection and reviews the literature regarding the association of HSV with cervical cancer.